DOI: 10.14232/phd.10230
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Hybrid Approach to Chronic Total Coronary Occlusion Percutaneous Coronary Intervention

Abstract: Percutaneous coronary intervention (PCI) for chronic total occlusion (CTO) continues to evolve constantly with developing equipment and techniques. The hybrid approach to CTO PCI advocates dual coronary injection, careful and structured review of the angiogram, and flexibility. Use of all crossing strategies [antegrade wire escalation, antegrade dissection re-entry and retrograde approach] is encouraged, with initial and subsequent choices influenced by the CTO anatomic characteristics and the outcomes of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
0
10
0
2
Order By: Relevance
“…Several observational studies 26–31 and two RCTs 32,33 have reported that successful CTO PCI is associated with improvement in the quality of life, reduced need for CABG, improved left ventricular (LV) function, and LV reverse remodeling compared with failed revascularization. The retrograde approach is currently an essential tool for achieving high success rates, especially in complex lesions where the antegrade approach is not technically feasible or fails 34 . According to the hybrid algorithm, proximal cap ambiguity, poor‐quality distal vessel and the presence of interventional collaterals favor the use of the retrograde approach 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Several observational studies 26–31 and two RCTs 32,33 have reported that successful CTO PCI is associated with improvement in the quality of life, reduced need for CABG, improved left ventricular (LV) function, and LV reverse remodeling compared with failed revascularization. The retrograde approach is currently an essential tool for achieving high success rates, especially in complex lesions where the antegrade approach is not technically feasible or fails 34 . According to the hybrid algorithm, proximal cap ambiguity, poor‐quality distal vessel and the presence of interventional collaterals favor the use of the retrograde approach 35 .…”
Section: Discussionmentioning
confidence: 99%
“…As previously described, the antegrade approach remains the most commonly used CTO crossing technique 3,14‐17 . Higher lesion complexity (higher J‐CTO score, in‐stent restenosis, distal cap at bifurcation, proximal cap ambiguity, moderate/severe calcification, moderate/severe tortuosity and blunt/no stamp) were associated with utilization of larger number of guidewires.…”
Section: Discussionmentioning
confidence: 92%
“…Percutaneous coronary intervention (PCI) of coronary chronic total occlusions (CTOs) has evolved significantly during recent years, in large part due to developments in crossing techniques and advances in microcatheter and guidewire technology 1‐4 . Antegrade wiring remains the most common crossing strategy, 5 although more complex cases are more likely to require antegrade dissection and re‐entry and the retrograde approach 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Left main lesion (unprotected left main diseases) refers to the degree of left main coronary artery angiography stenosis greater than or equal to 50% of the lesions, and at the same time does not exist unblocked blood vessel bridge good collateral circulation or their right to left. CTO is a dynamic process from quantitative change to qualitative change after coronary artery atherosclerosis, the lesions usually begin with the rupture of the "vulnerable plaque" in the coronary arteries, forming clots at both ends of the plaque and which endly leading to complete occlusion of the coronary arteries [4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%